Tinjauan Yuridis terhadap Penggunaan Handphone saat Berkendara oleh Pengemudi Kendaraan Bermotor yang Membahayakan Pengguna Jalan Lainnya di Kota Kupang - Evarina Enjeli Patrisia Mau; Rudepel Petrus Leo; Darius Antonius Kian (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
The purpose of this study is to analyze the juridical review of the use of mobile phones while driving by motor vehicle drivers who endanger other road users in Kupang City. This research is an empirical juridical research in which this research is carried out in the Kupang City Resort Police Law Wilaya. This research uses interview guidelines for thirty-four sources. The results showed that law enforcement against motor vehicle drivers who use cellphones while driving. The inhibiting factors for the police in law enforcement against motor vehicle drivers who use cellphones while driving in Kupang City are internal and external factors. The efforts of the police in tackling cases of motorized vehicle drivers who use cellphones while driving in Kupang City are by strict enforcement, personal approach and conducting evaluations.